Prevalence of depression, anxiety and stress in medical residents from a Venezuelan hospital - Varela, Rey; Sánchez, María Elena; Méndez-Colmenares, Andrea; Ahumada, Alberto; Añez, Roberto; Salazar, Juan (Gaceta Médica de Caracas, 2021)
To determine the prevalence and severity of depression, anxiety, and stress in medical residents from the University Hospital of Maracaibo, Venezuela. Materials and methods: We conducted an observational, descriptive, and cross-sectional study among medical residents from the University Hospital in Maracaibo, Venezuela from March 2018 until June 2018. Prevalencia de depresión, ansiedad y estrés en médicos residentes de unhospital venezolano Determinar la prevalencia y severidad de depresión, ansiedad y estrés en médicos residentes del Hospital Universitario de Maracaibo, Venezuela. Materiales y métodos: Se realizó un estudio observacional, descriptivo y transversal en médicos residentes del mencionado hospital durante el período marzo 2018 a junio 2018.